2021
DOI: 10.3389/fneur.2021.651592
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and White Matter Suppression Imaging and Voxel-Based Morphometric Analysis in Conventional Magnetic Resonance Imaging-Negative Epilepsy

Abstract: Purpose: Delineation of subtle lesions in magnetic resonance imaging (MRI)-negative patients is of great importance in preoperative epilepsy evaluation. The aim of our study was to explore the diagnostic value of the novel fluid and white matter suppression (FLAWS) sequence in comparison with a voxel-based MRI postprocessing morphometric analysis program (MAP) in a consecutive cohort of non-lesional patients.Methods: Surgical candidates with a negative finding on an official neuroradiology report were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Two 3D sets with isotropic 1 mm 3 voxel are acquired in an interleaved acquisition scheme with two different inversion times (TI): TI 1 suppresses the white matter signal and TI 2 suppresses the CSF signal. From both data sets, a set of synthetic minimum FLAWS contrast images is calculated which can be regarded as a gray matter specific image [ 41 , 42 ] (Fig. 1 ).…”
Section: Key Sequencesmentioning
confidence: 99%
“…Two 3D sets with isotropic 1 mm 3 voxel are acquired in an interleaved acquisition scheme with two different inversion times (TI): TI 1 suppresses the white matter signal and TI 2 suppresses the CSF signal. From both data sets, a set of synthetic minimum FLAWS contrast images is calculated which can be regarded as a gray matter specific image [ 41 , 42 ] (Fig. 1 ).…”
Section: Key Sequencesmentioning
confidence: 99%
“…The evaluation of ipsilateral clusters remains a matter of debate, as the extent of an FCD can ultimately be defined only to a limited extent even employing current morphometric postprocessing. Previous studies using MAP have reported a sensitivity/specificity of 90%/67% based on MPRAGE sequences 9 and 43%/87% based on the FLAWS sequence 25 . In another study comparing MAP based on MPRAGE and MP2RAGE sequences, 10% of FCDs were visible only on MAP junction maps based on MP2RAGE sequence 11 .…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies using MAP have reported a sensitivity/specificity of 90%/67% based on MPRAGE sequences 9 and 43%/87% based on the FLAWS sequence. 25 In another study comparing MAP based on MPRAGE and MP2RAGE sequences, 10% of FCDs were visible only on MAP junction maps based on MP2RAGE sequence. 11 In a study by Wang et al examining a 7-T MAP based on the MP2RAGE sequence, 25% more lesions were detected compared to a 3-T MRI MAP based on the MPRAGE sequence.…”
Section: Discussionmentioning
confidence: 97%
“…Figure 5 describes a case of conventionally MRI-negative PET-positive unilateral TLE, in which increased DIR signals can be found in the focus side, while it was difficult to detect on FLAIR, T1WI, and T2WI. More recently, fluid and white matter suppression (FLAWS) has been reported for better visualization of focal cortical dysplasia even in conventionally MRI-negative cases ( Chen et al, 2018a ; Sun et al, 2021 ). FLAWS suppresses the white matter and cerebrospinal fluid signals and then generate gray matter-specific images ( Tanner et al, 2012 ; Chen et al, 2018a ).…”
Section: Advanced Structural Imagingmentioning
confidence: 99%